Akomodasi dan Atribusi Penggunaan Eufemisme dan Disfemisme dalam Pojok Kampung JTV: Kajian Komunikasi Linguistik - Mafasi Eryawan Krisnuwardhana; Irma Mufita Yulistiowati (Universitas Merdeka Malang, 2023)
The use of language in mass media, especially news programs on television, must follow appropriate linguistic rules in order to maintain the values of politeness and appropriateness, as a spectacle for the general public. However, something different happened to one of the news programs broadcast by JTV, namely Pojok Kampung. Corner Village actually has a typical Suroboyoan linguisticcharacter which is considered very rude, impolite, outspoken, vulgar and egalitarian which can be studied from a linguistic perspective, especially euphemisms and dysphemisms. The methodologyused in this research was the collection of euphemisms and dysphemisms in 39 Pojok Kampung news stories. This research finds out how euphemisms and dysphemisms are accommodated in communication, by looking at the attribution process.